Frequency of autoimmune-associated exogenous psychoses in routine clinical care - Maria Buthut; David Haslacher; Surjo R. Soekadar; Felix Machleid; Jakob Kaminski; Philipp Reber; Johanna Schoener; Anna Pichler; Moritz Thiele; Jochen Michely; Helle Foverskov-Rasmussen; Irina Baskow; et al. (Brain, Behavior, & Immunity - Health)
Background: Psychosis occurs in a wide spectrum of mental and somatic disorders, with autoimmune processes being a potentially underdiagnosed cause. Clinical warning-signs can help identifying autoimmune encephalitis (AIE) or psychosis (AIP). Here we evaluated warning-signs and biomarkers in patients experiencing acute psychotic episodes who were admitted to inner-city sectorized care with a focus on identifying autoimmune causes of psychosis. Methods: We analyzed data obtained from routine clinical care, including blood, urine, CSF, EEG, and MRI when available. CSF-analysis included screening for antineuronal autoantibodies using commercial antibody screening (CAS) and indirect immunofluorescence (IFT). Origin of psychosis was defined according to patients’ discharge diagnosis (ICD-10 criteria). Results: Within 39 months, 352 participants were included, 114 of them experienced their first episode of psychosis (FEP). In 139 patients, psychotic symptoms were attributed to exogenous origin (F0: N = 90; F1: N = 48), the others were diagnosed with categories F2, F3 and F4. Among the 139 patients, 3 patients had pleocytosis or other CSF abnormalities. CAS was positive in two patients in CSF, leading to a confirmed diagnose of AIP in only one case while evaluated as unspecific in the other. IFT determined the prevalence of IgG-autoantibodies in CSF in four patients, who had FEP. Symptoms improved following immunotherapy in three of the four diagnosed patients. Conclusion: CSF analysis suggested four cases with AIP, with only one detected through commercial assays. Despite the rather low prevalence of AIP in this community sample, the availability of specific treatment options underscores the importance of further research regarding in-depth diagnostic evaluation for autoimmune processes in patients with acute psychosis.